2004
DOI: 10.1111/j.0141-9889.2004.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

Structuring health needs assessments: the medicalisation of health visiting

Abstract: This paper draws on Foucault to understand the changing discourse and impact of structured 'health needs assessments' on health visiting practice. Literature about this activity makes little mention of the long-standing social purposes of health visiting, which include surveillance of vulnerable and invisible populations, providing them, where needed, with help and support to access protective and supportive services. Instead, the discourse has been concerned primarily with an epidemiological focus and public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…Although not identical, this shares many of the ideas and assumptions underlying the use of disease templates and indicators, introduced as part of the QOF in primary care, 284 which aim to provide a structure to the ways in which GPs monitor patients' lifestyle behaviours and prompt them to offer lifestyle advice to patients or to use structured needs assessments in social care and health visiting to ensure that certain topics are addressed with clients. 241,285 In summary, PROMs feedback is assumed to help clinicians monitor the impact of patients' treatment on their health, which in turn may lead to changes in treatment, referrals or further tests to explore the problem. It is thought that this in turn will lead to improved patient outcomes.…”
Section: Patient-reported Outcome Measures As Clinical Monitoring Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not identical, this shares many of the ideas and assumptions underlying the use of disease templates and indicators, introduced as part of the QOF in primary care, 284 which aim to provide a structure to the ways in which GPs monitor patients' lifestyle behaviours and prompt them to offer lifestyle advice to patients or to use structured needs assessments in social care and health visiting to ensure that certain topics are addressed with clients. 241,285 In summary, PROMs feedback is assumed to help clinicians monitor the impact of patients' treatment on their health, which in turn may lead to changes in treatment, referrals or further tests to explore the problem. It is thought that this in turn will lead to improved patient outcomes.…”
Section: Patient-reported Outcome Measures As Clinical Monitoring Toolsmentioning
confidence: 99%
“…302 Other studies have also highlighted the tensions between implementing standardised approaches to patient assessment and care and maintaining and building a relationship with patients. 241,284,285,368,369 Our review suggests that PROMs function more as a tool to support patients in raising issues with clinicians than they do in substantially changing clinicians' communication practices with patients. Patients valued both standardised and individualised PROMs as tools to do this, although our review also suggests that thought is required about which patients may benefit and which may not.…”
Section: Actionabilitymentioning
confidence: 99%
“…Hayter (2007) found that nurses' use of medico-statistical facts downgraded potential side effects. Cowley, Mitcheson, and Houston (2004) showed how the talk and work of home visiting nurses achieved the requirements of institutional agendas. 2.…”
Section: Problem Statementmentioning
confidence: 99%
“…Advocates of structured assessment tools emphasise how they are to be used in partnership with the patient who can be talked through a list of questions, prompts and triggers, which help the patient to think about their own needs (Cowley et al, 2004). Little is known about professionals' views and experiences of using assessment tools and some negative views have been reported about their use (Hughes et al, 2003;Baba et al, 2007).…”
Section: Introductionmentioning
confidence: 99%